Phenotypic, Biochemical Identification And Antibiotic Sensitivity Pattern Of Staphylococcus Species From Urinary Tract Infections Among Female Sheep Breeders And Ewes With Special Emphasis To Methicillin And Vancomycin Resistant Staphylococcus aureus - Hassan Beg, Areean Ibrahim; Al-Ezzy, Ali Ibrahim Ali; Al-Zubaidi, Raad Mahmood (Diyala Journal for Veterinary Sciences, 2024)
Aims: Isolation, phenotypic identification and antibiotic sensitivity pattern of staphylococcus species from urinary tract infections in female sheep breeders and ewes with special emphasis to methicillin and vancomycin resistant S. aureus Methods: A total of 120 urine samples were collected from female sheep breeders (49) and ewes (71) with signs of UTI were cultured on mannitol salt agar and subjected to full biochemical identification by Vitek 2 system. Methicillin resistance was detected by Cefoxitin Screen test and MecA gene was detected by PCR. Results: S. aureus was isolated from 3(4.83%), in female sheep breeders and 7(11.29%) among ewe. S. aureus shown (100%) resistance for Penicillines and Cephalosporins, Methicillin which confirmed early by detection of MecA gene. All MRSA was resistant to Polypeptides, (100%) for Vancomycin and 2/3, (66%) for Teicoplanin in female sheep breeders. In ewes, All MRSA was resistant to polypeptides antibiotics, (100%) for vancomycin and 6/7, (85.72%) for Teicoplanin. Resistance of S. aureus to macrolides antibiotics was detected in 1/7, (14.28%) for Azithromycin. Resistance of S. aureus to Lincosamides antibiotics, Clindamycin was detected in 1/7, (14.28%) Conclusion: Although, S. aureus constitutes a minimal in the form of frequency as a cause of UTIs in human and ewes, Methicillin and Vancomycin Resistant S. aureus should be considered seriously and potentially to get rid the possible sequels